SARS-CoV-2 Delta Variant in Jingmen City, Hubei Province, China, 2021: Children Susceptible and Vaccination Breakthrough Infection - Li, Dan; Li, Ai-e; Li, Zhu-qing; Bao, Yu; Liu, Tian; Qin, Xiang-Rong; Yu, Xue-jie (Frontiers in Microbiology, 2022)
Background: The Delta variant (B.1.617.2) of SARS-CoV-2 was the dominant viral strain causing COVID-19 in China, 2021. We reported a SARS-CoV-2 Delta variant outbreak in Jingmen City, Hubei Province, China. Methods: Data of epidemiological, clinical, laboratorial, and vaccination of COVID-19 cases were collected through field investigation and analyzed. Results: During the outbreak from August 4 to August 20, 2021, 58 cases of the SARS-CoV-2 Delta variant (B.1.617.2) were identified with 15 (25.9%) asymptomatic and 43 (74.1%) symptomatic (mild and moderate) patients. The mean serial interval was 2.6 days (standard deviation: 2.0, 95% CI: 1.9–3.6). The median age of the patients was 39 years (ranging from 1 to 60 years) with high proportion in children (19.0%). The secondary attack rate was 9.8% higher from parents to their children (<18 years) (46.2%, 95% CI: 14.8%–77.5%) than that between spouses (36.4%, 95% CI: 14.5%–58.2%), but no significant difference was observed (P>0.05). Approximately half (27; 46.6%) of cases were vaccine breakthrough infections. In vaccine breakthrough cases (fully vaccinated), viral loads decreased 1.9–3.4 fold (P<0.05), and duration of viral shedding shortened 5 days (P<0.05), and the risk of becoming symptomatic from asymptomatic decreased 33% (95% CI: 5%–53%) (aged ≥12 years) than those in unvaccinated infections. Conclusions: Children are highly susceptible to the SARS-CoV-2 Delta variant in the COVID-19 outbreak in Jingmen City in 2021. Inactivated vaccine derived from wide-type strain can effectively reduce the viral load, duration of viral shedding, and clinical severity in vaccine breakthrough cases. Our study indicates that protective measures including fully vaccination against COVID-19 especially in children should be strengthened.